A study of some addition chain problems - Tsai, Y.H.; Chin, Y.H. (International journal of computer mathematics, 1987)
In this paper, some mathematical properties of the shortest-length addition chain are found for certain integers whose binary patterns meet some special forms; and the correctness of these properties is proved.